Pixmath / Bibi Qashrina ... [et al.] - Qashrina, Bibi; Abdul Rahman, Nurlyn Syahirah; Hassim, Putri Irdina; Kamal Azmil, Farah Shahira (2022)
Gamification is becoming more popular in academic contexts. Gamification theory in education states that students learn more effectively when they are having fun at the same time. Moreover, they learn best when they have goals, targets, and achievements to strive for. PixMath is a physical educational board game that aims to encourage children 8 to 12 years old to practice and improve their arithmetic skills in a fun and interactive way. Its creation is motivated by a mathematical counting game known as Picture Cross. In PixMath, the players are required to fill up empty numbered grids to complete a chosen picture and win the game by solving arithmetic questions. The arithmetic questions are classified into three levels: easy, intermediate, and difficult questions. A survey that was conducted on a group of students who played PixMath has received positive feedback. Some students claimed that the game is interesting, and exciting and has helped them improve their arithmetic skills. Hence, it has a high potential to be commercialized as a physical-mathematical board game in the market.